Biofiltration Efficiency of Algae Spirogyra hyalina to Reduce Salinity of Sea Water - Putra, Ayub Wirabuana (International Journal of Applied Biology, 2017)
Algae Spyrogyra hyalina is one species of fresh water algae that is very easy to find in Indonesia. This species of algae known to have a lot of potential, which until now unknown. One potential that tried to explore in this research is the ability of these algae for decreasing the level of salt water salinity into fresh water. This research is an experiment with a completely randomized design (CRD), three treatments and three replications. Testing is done by performing algae arbsorbtion using three forms (powder, granule, and paper) with different biomass (1 g, 2 g, and 4gr). Preparations then coupled into a transparent pipe. The results showed the real effect of the decreased levels of salinity brine through the circuit. Filter with the powder forms with 4gr biomass has the highest salinity level reduction of 15%o, Â then the dosage form of granules with biomass 4gr with decreased 5.23%o and the third dosage form of paper with 1 gram of biomass with a decrease of 4.23%o.Forms with other biomass have a decrease in the salinity level of not more than 4%o. Preparations with powder form and 4gr biomass can be used to reduce the salinity level in the salt water.